Organization of innovative activities in telecommunications enterprises - Muazzamkhon Shaislamova , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the context of the global pandemic, the rapid penetration of information technology in all spheres of economic activity, increasing demand for online sales of services and goods, leads to the important role of telecommunications companies in the national economy. The main role of the telecommunications sector is reflected in the essence of the impact of the national economy on the process of transition to innovative development. This, in turn, requires the development of innovative activities of telecommunications enterprises that meet the requirements of the current stage of development, taking into account the impact of internal and external factors that threaten the innovative development of the country. In general, the innovation process consists of obtaining and commercializing inventions, new technologies, types of products and services, production, financial, administrative or other decisions and other results of intellectual activity.